Role of natural killer cells in antitumor resistance - Kaneno, Ramon [UNESP] (My University, 2005)
Natural killer cells constitute a population of lymphocytes able to non-specifically destroy virus-infected and some kinds of tumor cells. Since this lytic activity was shown by non-immunized animals the phenomenon is denominated natural killer (NK) activity and contrasts with specific cytotoxicity performed by cytolytic T lymphocytes (CTLs) because it does not depends on MHC-restricted peptides recognition. In fact, the main feature of most functional receptors of NK cells (NKRs) is their ability to be inhibited by different kinds of class I MHC antigens. In the middle of the 1950's, Burnet & Thomas forged the concept of tumor immunosurveillance and NK cells can be considered one of the main figures in this phenomenon both for effector and regulatory functions. In the present review the early studies on the biology of NK cells were revisited and both their antitumor activity and dependence on the activation by cytokines are discussed.
Keywords: Cell activation; Cytotoxicity; Natural killer; Tumor immunology; batroxobin; gangliotetraosylceramide; interferon; interleukin 12; interleukin 15; interleukin 21; interleukin 23; interleukin 4; interleukin 6; monoclonal antibody; monoclonal antibody pk 136; perforin; recombinant alpha interferon; tumor necrosis factor alpha; unclassified drug; acute myeloblastic leukemia; angiogenesis; antigen recognition; antineoplastic activity; blood clotting disorder; bone marrow transplantation; Burkitt lymphoma; cancer cell culture; cancer growth; cancer immunology; cancer immunotherapy; cancer infiltration; cancer inhibition; cancer patient; cancer resistance; cancer susceptibility; colon carcinogenesis; colon carcinoma; colorectal carcinoma; dendritic cell; diarrhea; effector cell; host resistance; human; immunosurveillance; liver metastasis; lung disease; lung metastasis; lymphokine activated killer cell; melanoma cell; metastasis inhibition; natural killer T cell; nonhuman; review; skin toxicity; T lymphocyte subpopulation; thrombocytopenia; Animalia